Rancang Bangun Pengukur Kecepatan Angin Berbasis Arduino untuk Terowongan Angin Low Subsonic - Buyung Junaidin; Anggraeni Kusumaningrum; Wisnu Prayogih; Yosep Reo (Aviation Electronics, Information Technology, Telecommunications, Electricals, Controls (AVITEC), 2022)
The wind speed gauge in a wind tunnel plays an important role in the airflow simulation process so that it is similar to the actual conditions as desired. Wind speed measurement in wind tunnel mostly use manometer with special fluid (red manometer fluid) and the resulting data is in the form of analog data. The red manometer fluid is unavailable in Indonesia and its price is quite expensive so it becomes a challenge for wind tunnels that still use manometer. Therefore, it is necessary to make a new instrument for measuring wind speed that is easy to use by utilizing materials that are easily obtained but still apply the same measurement principles as a manometer in measuring wind speed in wind tunnels. The design of the wind speed measuring device can take advantage of microcontroller technology. The wind speed sensor design process goes through three stages including hardware design, software design, and system design. The hardware used for the system are an Arduino Uno R3 microcontroller, a differential pressure sensor MPXV7002DP, and an LCD. Research results obtain a wind speed sensor that can be used to measure wind speed in a low subsonic wind tunnel based on Bernoulli's principle that utilizes a pitot tube with a maximum speed of 30m/s. The wind speed sensor is an Arduino-based design that can display the wind speed measurement results on the LCD screen. The wind speed sensor was declared valid to be used to measure wind speed because there were no deviations from the wind speed measurement when compared to the measurement results from a calibrated anemometer.